Soil Ventilation Benefited Strawberry Growth via Microbial Communities and Nutrient Cycling Under High-Density Planting - Zhang, Yan; Hu, Yujing; You, Zijing; Li, Zhenglin; Kong, Miao; Han, Mingzheng; Liu, Zhimin; Zhang, Jie; Yao, Yuncong (Frontiers in Microbiology, 2021)
In order to increase O2 concentration in the rhizosphere and reduce the continuous cropping obstacles under high-density cultivation, ventilation is often used to increase soil aeration. Yet the effect of ventilation on soil microbial communities and nutrient cycling, further the extent to which they influence strawberry growth under greenhouse conditions are still poorly understood. Thus, four treatments—no ventilation+low planting density (LD), ventilation+LD, no ventilation+high planting density (HD), and ventilation+HD—of strawberry ‘Red cheeks’ (Fragaria×ananassa Duch. cv. ‘Benihopp’) were studied in a greenhouse for three years. The ventilation pipe (diameter=10 cm) was buried in the soil 15 cm depth from the surface and fresh air was sent to the root zone through the pipe by a blower. Ten pipes (one pipe line in a row) were attached to a blower. Soil samples were collected using a stainless-steel corer (5-point intra-row sampling) for the nutrient and microbial analyses. The composition and structure of the soil bacterial and fungal communities were analyzed by high-throughput sequencing of the 16S and 18S rRNA genes, and functional profiles were predicted using PICRUSt and FUNGuild, respectively. The results showed that soil ventilation increased the net photosynthetic rate, transpiration rate, and water use efficiency of strawberry plants across two growth stages (vegetative growth stage and fruit development stage). Soil ventilation increased its available nutrient contents, but the available nutrient contents were reduced under the high planting density compared with low planting density. Both the O2 concentration and O2:CO2 ratio were increased by ventilation; these were positively correlated with the relative abundance of Bacilli, Gamma-proteobacteria, Blastocatella as well as Chytridiomycota and Pezizomycetes. Conversely, ventilation decreased soil CO2 concentration and the abundance of Beta-proteobacteria and Gemmatimonadetes. The greater planting density increased the relative abundance of Acidobacteria (oligotrophic group). Ventilation altered soil temperature and pH along with carbon and nitrogen functional profiles in the vegetative growth stage (more nitrogen components) and fruit development stage (more carbon components), which benefited strawberry plant growth under high planting density. The practice of soil ventilation provides a strategy to alleviate hypoxia stress and continuous cropping obstacles for improving crop production in greenhouse settings.